1968
DOI: 10.1136/bmj.2.5602.390
|View full text |Cite
|
Sign up to set email alerts
|

Folate status and requirement in pregnancy.

Abstract: SummarySome controversial aspects of rheumatic heart disease are discussed in the light of personal experience in Edinburgh. Symptoms are not always a reliable guide to severity, and the correct time for surgical treatment should be based on an objective assessment. Dangers of delay include progressive damage to the pulmonary circulation, lungs, right ventricle, and liver, and the risks of systemic embolism, pulmonary oedema, and pulmonary infarction.The New York Heart Association classification of disability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
38
1
4

Year Published

1977
1977
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(47 citation statements)
references
References 15 publications
(6 reference statements)
4
38
1
4
Order By: Relevance
“…The recommendation was again increased to 400 mg/d (200 mg from food folate and 100 mg from folic acid) in 1998 (53), after the bioavailability of food folate and folic acid (pteroylmonoglutamic acid, which has two-fold the bioavailability of food folate) was considered. The study on "folate status and requirement in pregnancy" was published in 1968 (54). In the report, based on serum folate levels in non-pregnant women, the authors calculated a dose of an additional 100 mg of folic acid (equivalent to 200 mg food folate) needed during pregnancy.…”
Section: Folatementioning
confidence: 99%
“…The recommendation was again increased to 400 mg/d (200 mg from food folate and 100 mg from folic acid) in 1998 (53), after the bioavailability of food folate and folic acid (pteroylmonoglutamic acid, which has two-fold the bioavailability of food folate) was considered. The study on "folate status and requirement in pregnancy" was published in 1968 (54). In the report, based on serum folate levels in non-pregnant women, the authors calculated a dose of an additional 100 mg of folic acid (equivalent to 200 mg food folate) needed during pregnancy.…”
Section: Folatementioning
confidence: 99%
“…This result agrees with our figure of 4 times the expected frequency of small-for-dates babies born to mothers with a serum folate level <5 jug/l. On the other hand, Chanarin et al (1968) and Varadi et al (1966) reported that megaloblastic anaemia of pregnancy had no adverse effect on the infant's birthweight. These results could perhaps be explained, if the diagnosis of megaloblastic anaemia (and folate deficiency) had been made before the last month of pregnancy and therefore presumably the mothers had been treated for some time before they actually delivered.…”
Section: Discussionmentioning
confidence: 99%
“…In general, RBC folate values fall during pregnancy; if folate supplements are given, RBC folate values remain constant or may even rise during pregnancy (7,9). The effect of folate supplementation during pregnancy on infant birth weight has been studied in a number of human population groups.…”
Section: Discussionmentioning
confidence: 99%